The statoliths of Catostylus tagi, chemical characterization by energy dispersive X-ray spectroscopy - Santos, Gonçalo (2018)
2nd International Congress of CiiEM: “Translational Research and Innovation in Human in health Sciences”. Egas Moniz, Caparica, 11-13 June 2017